A pilot study on interaction between donkey tetherin and EIAV stains with different virulent and replication characteristics. (May 2017) - Yao, Qiucheng; Ma, Jian; Wang, Xuefeng; Guo, Miaomiao; Li, Yanfei; Wang, Xiaojun
Abstract: Tetherin (BST-2) is an important host restriction factor that can inhibit the release of a diverse array of enveloped viruses from infected cells. Conversely, to facilitate their release and spread, many viruses have evolved various strategies to overcome the antiviral effect of tetherin in a species-specific manner. During the development of an attenuated equine infectious anemia virus (EIAV) vaccine in our laboratory, we found that serial passage of a field-isolated virulent EIAV strains in horse and donkey as well as the cultivated donkey cells, produces several typical EIAV strains, including EIAVDV, EIAVDLV, and EIAVFDDV, which exhibit distinct virulence and replication features in vivo and in vitro . However, the role of host restriction factors in EIAV evolution during the serial passage is not well understood. This study aimed to evaluate whether these newly generated strains adapt differently to donkey tetherin (do-tetherin) based on their virulence. We found that do-tetherin exerts an inhibition on the release of the viral particles produced by all three strains, albeit with varying intensity: EIAVDV  < EIAVDLV  < EIAVFDDV . Additionally, all three EIAV strains could counteract the restriction mediated by do-tetherin via their envelope proteins (Env) with varying strength: EIAVDV  > EIAVDLV  > EIAVFDDV . These results indicate that donkey tetherin is involved in shaping of EIAV evolution during serial passage. Highlights: It is the first time to use a lentivirus attenuation system to investigate the interaction between lentiviruse and host innate immune restriction factors. Do-Tetherin differently restricted the budding of virulent EIAV strains with different evolution levels. Env proteins of the three EIAV strains with different virulent and replication characteristics all can antagonize the restriction of do-Tetherin, but the antagonization effects declined from the virulent strain to the attenuated strains.